2010
DOI: 10.1080/10601325.2011.528307
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Nano-silica/Polyacrylate Composite Emulsions by Sol-gel Method andin-situEmulsion Polymerization

Abstract: Organic nano-silica was firstly synthesized by sol-gel method with methyl methacrylate (MMA) and butyl acrylate (BA) in the micelles as dispersing media, tetraethoxysilicate (TEOS) as precursor, hydrochloric acid as catalyst and methacryloylpropyl trimethoxysilane (A174) as modifier. Subsequently, the nano-silica/polyacrylate composite emulsions were directly prepared by in-situ emulsion polymerization under the action of the initiator. The structure and properties were characterized by Fourier transform infra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 18 publications
(15 reference statements)
2
6
0
Order By: Relevance
“…Using mid-IR analysis, the changes on functional −OH group ratios was analyzed and significant reduction on intensity of peaks was observed after the filler silanization. These changes in the ratios confirmed the reduction of hydrophilic chemical structures in silanized fillers in accordance to prior studies [28,30]. Additionally, thermogravimetric analysis demonstrated that the silane mass concentration on the surface of the filler was silane-dependent, with the higher molecular weight thiourethane silane demonstrating the greatest mass loss via this method.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Using mid-IR analysis, the changes on functional −OH group ratios was analyzed and significant reduction on intensity of peaks was observed after the filler silanization. These changes in the ratios confirmed the reduction of hydrophilic chemical structures in silanized fillers in accordance to prior studies [28,30]. Additionally, thermogravimetric analysis demonstrated that the silane mass concentration on the surface of the filler was silane-dependent, with the higher molecular weight thiourethane silane demonstrating the greatest mass loss via this method.…”
Section: Discussionsupporting
confidence: 89%
“…Characteristic absorption bands of nano silica were observed at 1050 and 461 cm −1 due to the asymmetric and symmetric stretching vibration of Si–O–Si structure [28]. A broad sharp band at around 3455 cm −1 and a sharp band at 1636 cm −1 , observed in all samples, are associated with hydroxyl groups that are present on nano silica surface [2830]. Table 1 presents the peak intensity ratios of the main functional group (-OH) changed after silanization treatments.…”
Section: Resultsmentioning
confidence: 99%
“…Scheme 1 shows the diagram of the polymerization mechanism and the possible interactions between monomers and silica nanoparticles. It is expected that some of the silica nanoparticles cannot be converted to nanogel composites, as described by Ye et al [30] and Wenbo et al [31]. This expectation can be confirmed by different characterization techniques that are discussed in the forthcoming section.…”
Section: Resultssupporting
confidence: 57%
“…Moreover, the average diameter of silica was increased from 25 nm to 55.2 nm, 115.8 nm, and 158 nm with PAMPS-Na, PAMPS-Na/AAm, and PAAm, respectively. The average particle size and PDI values of PAMPS-Na/AAm and PAAm were increased and formed a broad peak to confirm the trapping or/and encapsulating of silica nanoparticles by the nanogel [30,32]. The interaction of nanoparticles with their surroundings and the stability of their dispersion in aqueous solvent were influenced by their surface charge [33,34].…”
Section: Characterization Of Silica-nanogel Compositesmentioning
confidence: 99%
“…Gold nanoparticles show surface plasmon resonance (SPR), Rayleigh scattering and surface-enhanced Raman scattering (SERS), which facilitates its applications in the fields of catalysis, optoelectronics, and medicine (Shankar et al, 2004). Although there are several bottom-up strategies for the synthesis of metal nanoparticles, they are mainly synthesized by chemical methods involving toxic compounds such as n-hexadecyltrimethylammonium bromide (HTAB), isopropanol, 2-ethoxyethanol, N-dimethylformamide (DMF), methyl methacrylate and butyl acrylate (Ye et al, 2011). Since the use of toxic chemicals plagues its use in biomedical applications and/or environmentally friendly processes, biological approaches for the synthesis of nanoparticles using microorganisms and plants are preferred.…”
Section: Introductionmentioning
confidence: 99%